Laying the foundations of a Christian identity: Tertullian of Carthage’s rhetoric on Marcion in ‘Adversus Marcionem’ - Garcia, Willian Fernandes; Selvatici, Monica (Romanitas - Revista de Estudos Grecolatinos, 2020)
In this article we analyze Tertullian of Carthage’s arguments concerning the “heretic” Marcion. By that, we are able to see how Christian identity was built up fundamentally by the rhetorical opposition between “true” Christianity against “false Christianities”, in this case represented by Marcionism. Relying on anthropologist Fredrik Barth’s theory of Ethnicity we are able to understand the process of construction (or deconstruction) of an adversary carried out by Tertullian at the same time as he built up the premises of his Christian identity through comparison between the ideas he judged correct in opposition to what was supposedly preached by his opponents.